Penetapan kadar fenolik total ekstrak kayu raru (Cotylelobium lanceolatum Craib) berdasarkan perbedaan konsentrasi etanol dengan metode spektrofotometri UV-Vis - Lastri Afni; Anny Sartika Daulay; Ridwanto Ridwanto; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Many Indonesian people use or use plants as traditional medicine; one plant that has many benefits is raru bark (Cotylelobium lanceolatum Craib), which is used as a traditional medicine in various diseases such as diarrhea, malaria, and diabetes. This study aims to find out what classes of compounds are found in raru bark extract and to determine the value of total phenolic levels contained in raru bark extract in various concentrations (96%, 70%, 50%). The stages of this research include processing plant materials, making raru bark ethanol extract, characterization examination, phytochemical screening, and determining total phenolic levels of raru bark extract based on differences in ethanol concentration by UV-Vis spectrophotometry method. The results showed that raru bark ethanol extract contains compounds, flavonoids, tannins, saponins, steroids, and phenolics. Determination of total phenolic content by determining the maximum wavelength of gallic acid and calculation of entire phenolic content by UV-Vis spectrophotometry method. Results of selecting the whole phenolic content of raru bark ethanol extract at a concentration of 96%; 28,6544±0,1548 mgGAE/g, 70%; 23,9682±0,1270 mgGAE/g, 50%; 20,5825±0,1993 mgGAE/g, then the phenolic content that best produces total phenolic levels is raru bark ethanol extract (Cotylelobium lanceolatum Craib) concentration of 96%.